2020
DOI: 10.1097/icu.0000000000000699
|View full text |Cite
|
Sign up to set email alerts
|

Orbital disease in neuro-ophthalmology

Abstract: Purpose of review Orbital disease represents a diverse spectrum of pathology and can result in a variety of neuro-ophthalmic manifestations. The aim of this review is to provide updates on recent advances in our understanding of orbital disease secondary to thyroid eye disease, myositis, IgG4-related disease, sarcoidosis, granulomatosis with polyangiitis and various tumours. Recent findings With regards to thyroid eye disease, there have been recent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Use of SCS is well established for optic neuritis and compressive optic neuropathy related to thyroid eye disease, both of which have a known inflammatory bases; however, ischemic and traumatic causes are more controversial 120,121 …”
Section: Optic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Use of SCS is well established for optic neuritis and compressive optic neuropathy related to thyroid eye disease, both of which have a known inflammatory bases; however, ischemic and traumatic causes are more controversial 120,121 …”
Section: Optic Neuropathymentioning
confidence: 99%
“…Use of SCS is well established for optic neuritis and compressive optic neuropathy related to thyroid eye disease, both of which have a known inflammatory bases; however, ischemic and traumatic causes are more controversial. 120,121 Traumatic optic neuropathy (TON) is relevant to the otolaryngologist in the setting of facial trauma. The 1999 International Optic Nerve Trauma Study found that SCS administered within 7 days of injury did not provide an advantage over no treatment; however, this study was nonrandomized with an uneven group distribution.…”
Section: Optic Neuropathymentioning
confidence: 99%